DIRECTIONS OF INCREASING THE COMPETITIVENESS OF TOURIST ACTIVITY - KALINICHENKO, SERGIY; KOLIESNIK, TETIANA; GROKHOLSKYI, VADYM; GRIBINYK, ANDREY (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Entrepreneurship in the field of tourism and hospitality is mostly characterized by a high level of competition. The degree of market development, the complexity of working on it is largely dictated by the peculiarities of the competitive environment. With the transition to market relations, the creation of independent economic structures and the independence of enterprises and organizations found themselves in a difficult position. Today the situation is that the real need for tourist services is low due to the high cost and non-compliance of their quality with world standards. Thus, the specifics and features of competition in tourism due to the close relationship and interdependence between different levels competition in tourism. The synergistic effect of the competitiveness of the tourist system appears when competitiveness is ensured at all levels. When developing concepts for increasing competitiveness at any level of tourism, it is necessary to use a systematic approach and coordinate the competitiveness of tourism market participants at all levels. With the correct organization of coordination between the subjects of the tourist market can be significantly increased competitiveness of the tourist system as a whole. In order to effectively develop, maximize its competitive potential, stand out from other destinations, the tourist center must have a science-based sustainable development strategy, which serves as a roadmap for managing the region's tourism industry in the context of overall socio-economic progress and environmental well-being. The tourism business is directly dependent on the specific actions of the whole set of enterprises that are part of the chain of the process of creating a tourism product. These entities can be controlled only within the tourism cluster, which is an effective means of improving the quality of the tourism product during its development.
Keywords: tourism; region; destination; tourist product; competitiveness